Analisis Kesesuaian Pemanfaatan Ruang Terhadap RTRW di Kawasan Simpang Elak Kota Lhokseumawe - Qanitatul Isra Qamal; Muhammad Shofwan Azmy; Dinda Rizki Fadilah; Ardista Dwi Agustin; Ahmad Hidayat (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The Simpang Elak area in Lhokseumawe City is an important part of the urban spatial system, experiencing fairly intensive activity growth. This development dynamic has the potential to influence patterns of land use, making it necessary to assess its conformity with the Lhokseumawe City Spatial Plan (RTRW) for 2024–2044. This study aims to examine the level of conformity of land use in the Simpang Elak area with the applicable spatial planning regulations. The research method involved reviewing RTRW documents, analyzing zoning maps, and direct field observations of existing conditions. The analysis focused on land use designation, the types of activities developing, and the intensity of land use. The results indicate that land use in the Simpang Elak area generally follows the RTRW guidelines, particularly in trade and service areas. However, some forms of land use were still found to be partially inconsistent with zoning provisions and spatial intensity limits. This situation highlights the need to strengthen land use control to ensure that development in the Simpang Elak area proceeds in line with spatial planning regulations and supports the creation of an orderly, safe, and sustainable urban environment.